IMPLEMENTATION OF THE FORWARD CHAINING METHOD FOR DETECTING SCHOOL READINESS IN CHILDREN - Rorimpandey, Gladly C.; Mantik, Felitia Theona Geofani; Hasibuan, Alfiansyah (Informatika, Universitas Jenderal Soedirman, 2024)
Primary school education is the education of children aged 7 to 13 years as education at the basic level which is developed in accordance with educational units, regional potential and socio-culture. School readiness for children is no less important because in fact school readiness for children is very important for children because many children are found to be still not ready. attended school when but was already in elementary school. To overcome this problem, this research provides a solution by building an expert system for detecting school readiness in children using the forward chaining method, which is a technique in an expert system that begins with gathering information starting from collecting premises which is followed by a conclusion or derived information (then). From the results of testing using functional testing and usability testing, it is known that in implementing the forward chaining method, 24 symptoms of school readiness were identified based on knowledge obtained directly from psychologists. The results obtained in testing using usability testing based on the results obtained are assessed as final and then the average value is calculated. The final conclusion of the results determined through the SUS Score assessment is 84%. This shows that this system easy and useful in assessing children's school readiness. The implication of the results of this test is that the school readiness detection expert system can be a useful tool for parents, teachers to evaluate children's readiness to enter elementary school.